Hack the Cybersecurity Interview navigate cybersecurity interviews with confidence, from entry-level to expert roles - Foulon, Christophe; Underhill, Ken; Hopkins, Tia (Packt Publishing, 2024)
Chapter 4: Penetration Tester -- What is a Pentester? -- How much can you make in this role? -- What other careers can you pursue? -- Common interview questions for a pentester career -- Summary -- Chapter 5: Digital Forensic Analyst -- What is a digital forensic analyst? -- How much can you make in this career? -- What other careers can you pursue? -- Common interview questions for a digital forensic analyst career -- Summary -- Chapter 6: Cryptographer/Cryptanalyst -- What is a cryptographer? -- How much can you make in this career? -- What other careers can you pursue?
Keywords: Computer security / Vocational guidance; Employment interviewing; Sécurité informatique / Orientation professionnelle; Entretiens d'embauche